Exploring the impact of compound retrieval strategy in the task-switching paradigm - Fangyuan Zhou; Fangyuan Zhou (Frontiers in Human Neuroscience)
IntroductionTask-switching costs are commonly used to measure cognitive control. However, previous research has shown that when participants are not explicitly instructed on task rules, they can adopt the compound retrieval strategy in task-switching paradigms with limited targets, where task-switching costs cannot reflect cognitive control. Nevertheless, it remains unclear whether participants would spontaneously use the compound retrieval strategy when they are explicitly instructed on task rules. This study aimed to investigate this issue.MethodsIn the experiment, 36 participants were recruited to complete two conditions: the four-target condition, in which only four targets were presented and repeated throughout the experiment, and the infinite-target condition, where targets were not repeated.ResultsThe results revealed that, compared to the infinite-target condition, task-switching costs were smaller, while response-congruency effects and the N2 difference wave (incongruent trials—congruent trials) were larger in the four-target condition.DiscussionThese findings suggest that participants spontaneously use the compound retrieval strategy in the task-switching paradigm with limited targets.